Efficacy and safety of terbinafine hydrochloride 1% cream vs eberconazole nitrate 1% cream in localised tinea corporis and tinea cruris - Sanjiv V Choudhary; Taru Aghi; Shazia Bisati (Indian Dermatology Online Journal, 2014)
Aims: To study and compare the efficacy and safety of topical terbinafine hydrochloride 1% cream and eberconazole nitrate 1% cream in localized tinea corporis and cruris. Methods and Materials: Patients were randomized after considering various inclusion and exclusion criteria into two groups. Group A (treated with terbinafine 1% cream for 3 weeks) and group B (treated with eberconazole 1% cream for 3 weeks). The sample size was of 30 patients with 15 patients in each group. Assessment of clinical improvement, KOH mount and culture was done weekly up to 3 weeks to assess complete cure. Results: On comparison between the two groups, it was observed that eberconazole nitrate 1% cream was as effective as terbinafine hydrochloride 1% cream at the end of first (Non-sisgnificant (NS); P = 0.608, 1.00), second (NS; P = 0.291,0.55), and third (P = 1.00, 1.00) weeks with statistically nonsignificant clinical and mycological values. In both the groups, clinically no significant local side effects were noticed. Conclusions: The newer fungistatic eberconazole nitrate 1% cream was as effective as the fungicidal terbinafine hydrochloride 1% cream. Both the drugs showed good tolerability with no adverse effects.